DETERMINATION OF NATURAL GAS PRICING THROUGH PIPELINE IN DOWNSTREAM BUSINESS ACTIVITIES FOR COMMERCIAL CUSTOMERS IN WORK AREA SOR II SOUTH SUMATERA-WEST JAVA (SSWJ) - Meutya Hanifah Darajah; Syamsul Irham; Darmasetiawan Hakim (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2021)
Indonesia is a developing country that still depends on fossil fuels. Natural gas is one of the energy sources used as an alternative fuel for Indonesia's future to support national energy needs. This is because the amount of natural gas reserves in Indonesia are still classified as safe for the next several decades with increasing demand. The government has imposed a gas price for industry of USD $ 6 per MMBTU in accordance with the implementation of Presidential Regulation Number 40 of 2016 concerning Natural Gas Pricing. This strategic policy is believed to be able to boost the competitiveness of the domestic manufacturing sector so that it will make a significant contribution to the national economy. However, on the business entity side, this policy is considered to be detrimental because it is still unclear about the government intensive that is given to business entities. The purpose of this study is to analyze a case regarding the determination of the downstream selling price of natural gas for industrial costumers which should be in accordance with the parameters of the downstream selling price of natural gas. The results (output) obtained from this study indicate the process of optimizing the selling price of natural gas in downstream business activities to obtain the ideal value.